Mapping sustainable irrigation development potential with renewable groundwater in Africa for reducing African food insecurity - (:unkn) unknown (My University, 2018)
In Africa, groundwater irrigation is considered a reliable and affordable means to increase food security. Areas equipped for groundwater irrigation in Africa have however, developed slowly since 1950 and remain very limited. To date, no studies have identified the sustainable development potential of irrigation with renewable groundwater across Africa. This study is based on two approaches to locate and quantify this potential. The quantitative hydrological approach is based on the estimation of the current crop irrigation need and available renewable groundwater for irrigation after all other water needs, including environmental, have been satisfied. This approach shows that the potential is 44.6 x 106 ha or 20.5% of the cropland over the continent. The environmental approach redefines the quantitative potential by considering a set of biophysical and socio-economic factors conducive to sustainable development of groundwater irrigation. The potential is then 19.3 x 106 ha and it is reduced mainly from the equatorial regions where the need for irrigation is limited. In fact, without considering the countries of the Maghreb and South Africa where current irrigation by groundwater exceeds the estimated potential, groundwater irrigated areas could be multiplied by 75. The largest areas which are worthwhile to develop are mainly located along a west-east line from Angola to the north of Mozambique and a line south of the Sahel. The dry regions of the Sahel, East Africa and Southern Africa have limited development potential which is more suitable to small-scale agriculture and could greatly improve food security in Africa.
Keywords: African Research